SISTEM PENJUALAN BERBASIS WEB DI PT GLOBAL KARYA CEMERLANG - Dani; A. Nurul anwar; Dede Supriyadi; Ahmad Fikri Zulfikar (Journal of Research and Publication Innovation, 2025)
PT GLOBAL KARYA CEMERLANG (Hexro) is a company engaged in household sales. The need for medical equipment and health support equipment in the country is very large, this is the basis for the presence of this company. Apart from that, developments in health technology are needed to answer new challenges. Armed with a pre-formed marketing network, the health support tools offered by the company are very easily accepted by the public because their specifications are higher than similar products and are offered at very competitive prices. Sales data processing is still carried out manually, consumers have to come directly to the place to purchase products and make cash payment transactions, this makes the process of recapping reports on purchases from suppliers and sales to consumers difficult in making reports, this is because they have to recap all transactions that occurred during the reporting period you want to make. Therefore, this research aims to provide a solution by designing a web-based sales system using the PHP programming language [1] and a MySQL database. Where the author carried out system development using the waterfall method and used use case diagrams, activity diagrams and class diagrams. This research produces a solution in the form of a web-based sales system that can provide detailed product information to customers and can carry out purchase transactions anywhere and at any time.[2]